2020
DOI: 10.1101/2020.04.13.034645
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cyclopamine sensitizes Glioblastoma cells to Temozolomide treatment through Sonic Hedgehog pathway

Abstract: AimGlioblastoma is an extremely aggressive glioma, resistant to radio and chemotherapy usually performed with temozolomide. One of the main reasons for glioblastoma resistance to conventional therapies is due to the presence of cancer stem-like cells. These cells could recapitulate some signaling pathways important for embryonic development, such as Sonic hedgehog. Here, we investigated if the inhibitor of the Sonic hedgehog pathway, cyclopamine, could potentiate the temozolomide effect in cancer stem-like cel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…However, the combination of acepromazine and TMZ enhanced the dryness and drug resistance of GBM cells by inducing the expression of SOX-2 and OCT-4 and may lead to tumor recurrence in patients (134). Therefore, the best therapeutic strategy is to first inhibit the SHH pathway and then administer TMZ (134,135). Liu et al (136) found that the combination of capsulated propylamine and TMZ had synergistic cytotoxic effects and was more likely to inhibit the ability to induce apoptosis and eliminate neuroglobin formation by inhibiting GLI1 expression.…”
Section: Targeting the Hh Signaling Pathway In Gbmmentioning
confidence: 99%
“…However, the combination of acepromazine and TMZ enhanced the dryness and drug resistance of GBM cells by inducing the expression of SOX-2 and OCT-4 and may lead to tumor recurrence in patients (134). Therefore, the best therapeutic strategy is to first inhibit the SHH pathway and then administer TMZ (134,135). Liu et al (136) found that the combination of capsulated propylamine and TMZ had synergistic cytotoxic effects and was more likely to inhibit the ability to induce apoptosis and eliminate neuroglobin formation by inhibiting GLI1 expression.…”
Section: Targeting the Hh Signaling Pathway In Gbmmentioning
confidence: 99%